Aquinas and the 'Genius of Woman'. Issue 4 (October 2017) - Newton, William
Aquinas views women as inferior to men at a natural level in some respects. While affirming unity of species and hence an essential equality, he views women as intellectually inferior. This article considers the root cause of this position and argues that we must make a distinction between a twofold inheritance that was bequeathed by Aristotle to Aquinas. It is the erroneous embryology of Aristotle that is the underlying cause of Aquinas's judgment of the inferiority of women because it divides the sexes into passive and active principles of human generation. Given Aquinas's metaphysical commitment to the superiority of act over potency, this necessarily leads to a judgment of inferiority and has far-reaching implications vis-a-vis a negative view of the intellectual capacity of women. However, there is an important metaphysical inheritance from Aristotle that, if carefully separated from the erroneous physics (i.e. from the embryology), has the power to give credibility to the idea of the 'genius of woman', as popularized by John Paul II. A key element of this positive inheritance is the hylomorphic theory understood to include the notion of matter having some determinative impact on the substantial form.